ISLAM AND THE TWENTY-FIRST CENTURY - Muhammed Haron (International Institute of Islamic Thought, 1997)
On 4 June 1996, a plenary session was held at Groot Auditorium, in the Academy Building of Leiden University. This session was chaired by Professor Leertouwer, the vice-chancellor and rector of Leiden University (est. 1575), who also gave the opening address. In his speech, he emphasized the importance of the conference theme and referred to one of the most noteworthy and influential Dutch scholars, Snouck Hurgronje, who taught at the university between 1907 and 1921 and contributed to the field of Islamic studies in a unique manner. He then introduced Tarmizi Taher, Indonesia’s current minister of religious affairs, who delivered the opening address along with Abdelkabir Alaoui M'daghri, Morocco’s current minister of waqf and Islamic affairs, and a representative of the Netherland’s Ministry of Education, Culture, and Science. The minister of the Netherlands was not able to attend the conference. The Indonesian minister, a trained medical doctor, used his opening address to stress the importance of research in Islamic studies and to conantrate upon Dutch-Indonesian cooperation in this field. The Moroccan minister‘s speech was well received; the minister was added to the program at the last minute when it was learned that he would be visiting the country at that time. Tht title of his speech was “Coexistence in the New World Order.” A lawyer by training, he Ssed the issue of human rights and perfaced it by commenting upon the changes that have taken place over the centuries and the manner in which societies and communities took control of their circumstances. The keynote speaker, Riffat Hassan (University of Louisville, KY, USA) gave a speech titled “What Does it Mean to be a Muslim on the Eve of the Twenty-First Century?” A social anthropologist by training, she addressed the topic and drew quite a bit upon her own life history as a woman. The audience genedy found her feminist ideas to be very provocative and challenging. It was indeed unfortunate that one of the first parallel sessions was cancelled because one of the key participants fell ill. The other panelists for this session were fitted into other sessions. Atadah Bogdan Kopan ...